Effect of filler level and particle size on dental caries-inhibiting Ca–PO4 composite - Xu, Hockin H. K.; Weir, Michael D.; Sun, Limin; Ngai, Scott; Takagi, Shozo; Chow, Laurence C. (Journal of materials science. Materials in medicine, 2009)
Secondary caries and restoration fracture are common problems in restorative dentistry. The aim of this study was to develop Ca–PO 4 nanocomposite having improved stress-bearing properties and Ca and PO 4 ion release to inhibit caries, and to determine the effects of filler level. Nanoparticles of dicalcium phosphate anhydrous (DCPA), two larger DCPA powders, and reinforcing whiskers were incorporated into a resin. A 6 × 3 design was tested with six filler mass fractions (0, 30, 50, 65, 70, and 75%) and three DCPA particle sizes (112 nm, 0.88 μm, 12.0 μm). The DCPA nanocomposite at 75% fillers had a flexural strength (mean ± SD; n = 6) of 114 ± 23 MPa, matching the 112 ± 22 MPa of a commercial non-releasing, hybrid composite ( P > 0.1). This was 2-fold of the 60 ± 6 MPa of a commercial releasing control. Decreasing the particle size increased the ion release. Increasing the filler level increased the ion release at a rate faster than being linear. The amount of ion release from the nanocomposite matched or exceeded those of previous composites that released supersaturating levels of Ca and PO 4 and remineralized tooth lesions. This suggests that the much stronger nanocomposite may also be effective in remineralizing tooth lesion and inhibiting caries. In summary, combining calcium phosphate nanoparticles with reinforcing co-fillers in the composite provided a way to achieving both caries-inhibiting and stress-bearing capabilities. Filler level and particle size can be tailored to achieve optimal composite properties.